PENGUATAN PEMBELAJARAN AQIDAH AKHLAK MELALUI KITAB SULUK ASASI PADA SISWA KELAS X DI MADRASAH ALIYAH (MA) PENDIDIKAN ILMU AL QURAN SINGOSARI MALANG - Lutfi Setiawan, Dimas; Mutholingah, Siti; Rosidin, Rosidin; Carnawi, Carnawi (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study aims to describe in detail the implementation and outcomes of Aqidah Akhlak learning through the use of Kitab Suluk Asasi among tenth-grade students at MA Pendidikan Ilmu Al-Qur’an Singosari Malang. The research focuses on how this classical Islamic text is applied in the learning process and the extent to which it contributes to students’ educational achievements. The study employed a qualitative approach with a case study design, utilizing interviews, observations, and documentation to obtain comprehensive data. The findings reveal that the learning process was carried out by combining lectures, discussions, role modeling, and habituation methods. Kitab Suluk Asasi served as the primary reference that integrates theoretical knowledge with practical application, thereby enhancing students’ cognitive understanding of aqidah, fostering religious attitudes, and shaping more consistent Islamic behavior in their daily lives. Based on these results, it can be concluded that the use of classical texts remains relevant in contemporary Islamic education, particularly in strengthening character education, moral values, and the sustainable development of students’ Islamic personality.